Avaliação da efetividade do antígeno carboidrato CA 19-9 como biomarcador em modelo experimental de obstrução parcial do trato urinário - Shida, Márcia Emília Francisco (2021)
Introduction: Obstructive nephropathy, resulting from urinary tract obstruction during fetal development, represents the most common cause of kidney failure in infants and children. Despite the early intrauterine diagnosis, performed by prenatal ultrasound, the determination of the prognosis of the severity of the kidney injury is not well established yet. Therefore, the identification of blood and/or urinary markers to define the progression of renal damage would play an important role in deciding on earlier and more effective therapeutic interventions. Elevated carbohydrate antigen CA19-9 (originally a tumor marker) has been described in benign urinary obstruction. Aim: This study evaluated to which extent this easy-analysis biomarker could help in the earlier diagnosis, especially in doubtful cases, of obstructive uropathies with potential renal damage. We compared it to another biomarker, Lipocalin associated with neutrophil gelatinase (Ngal), related to the severity of the obstruction. Material and method: Forty-six female Wistar rats were divided into 5 groups, with different patterns of urinary tract obstruction: group control; group OIV: infravesical obstruction; group OIVd: infravesical obstruction with reversion, relief of the obstruction on the 7th postoperative day; group OUu: unilateral ureteral obstruction; group OUb: bilateral ureteral obstruction. The determination of CA 19-9, Ngal and creatinine basal in urine and blood was performed in the rats of the groups prior to surgery (T0). Surgical interventions promoted partial obstruction depending on the group. After 13 and14 days, new measurements (T1) of the markers were taken and compared to baseline values. Group OIVd underwent an intermediate (Ti) collection before clearance. Results: There was an increase in the urinary concentration of CA19-9 in all obstructed animals. In groups OIV, OUb and OIVd, the elevation at T1 and Ti, respectively, reached statistical significance in relation to the T0 value (p≤ 0,05). Changes in urinary CA19-9 were expressive in groups with infravesical obstruction. Relief of obstruction in group OIVd promoted a significant reduction in urinary CA19-9 values in the final evaluation with AUC=0.73. There was no positive correlation between the obstructed groups and serum CA19-9 levels. Conclusions: The urinary concentration of CA19-9 increased in the presence of partial urinary tract obstruction and there was a decline in urinary CA19-9 concentration after infravesical clearance.